In vitro evaluation of failure load of selected all-ceramic crowns / Ammar Mohammed Mohammed Al-Arwali - Ammar Mohammed, Mohammed Al-Arwali (2016)
Objective: The purpose of this study was to assess the fracture resistance and failure mode of three different all-ceramic crowns; CEREC Blocs, IPS e.Max Press and Cercon. Materials and Methods: Thirty extracted maxillary premolars were prepared and randomly allocated to 3 test groups (A, B and C; n = 10 for each group). For group A, monolithic feldspathic crowns were fabricated (CEREC Blocs, Sirona Dental). Group B consisted of monolithic lithium disilicate crowns (IPS e.Max Press, Ivoclar Vivadent). Group C consisted of bilayered partially stabilized zirconia crowns (Cercon, Degudent Dentsply). All crowns were cemented to their representative teeth via dual-cured resin cement (ParaCore, Coltène/Whaledent). The specimens were then subjected to thermocycling (5-55 ˚C/ 500 cycles) and loaded to failure at an angle of 45˚ to the occlusal surface of the crown. Failure data was statistically analyzed using one-way (ANOVA) test at α = 0.05. Fractoghraphic analysis was performed to determine the fracture modes of the failed specimens. Results: The mean fracture load values (N ± S.D.) for groups A, B and C were 387 ± 60 N, 452 ± 86 N, and 540 ± 171 N, respectively. Significant differences were found only between the failure loads of groups A and C (P < 0.05). Cracking that initiated from the cement layer surface resulting in bulk fracture was the major failure mode of group A. For group B & C, the major failure mode was similar, exhibiting catastrophic tooth fracture extending in a transverse plane from the buccal cervical area of crown to the palatal cervical area of root while the ceramic crown remained intact. Conclusion: Cercon crowns showed more fracture resistance than IPS e.Max Press crowns and CEREC Blocs crowns. IPS e.Max Press and Cercon crowns simulated similar major fractures; inducing severe distortion of the abutment teeth during occlusal loading. Furthermore, CEREC Blocs crowns showed catastrophic mode of ceramic fracture.